2015
DOI: 10.3389/fonc.2015.00106
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Fractionated Stereotactic Radiotherapy with or without Chemotherapy and Immunotherapy for Recurrent Glioblastoma Multiforme: A Single Institution Experience

Abstract: BackgroundThe current standard of care for salvage treatment of glioblastoma multiforme (GBM) is gross total resection and adjuvant chemoradiation for operable patients. Limited evidence exists to suggest that any particular treatment modality improves survival for recurrent GBM, especially if inoperable. We report our experience with fractionated stereotactic radiotherapy (fSRT) with and without chemo/immunotherapy, identifying prognostic factors associated with prolonged survival.MethodsFrom 2007 to 2014, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 53 publications
1
24
0
3
Order By: Relevance
“…However, many BM patients are eligible to SRS and it could be assumed that the good safety profile of BEV administration with a large radiation volume may also be expected in the context of its combination with smaller volume as in SRS. This assumption seems confirmed by some recent data of SRS combined with BEV in patients with recurrent malignant gliomas, confirming the feasibility of this approach with a good safety profile (5)(6)(7)(8). Clinical evaluation of BEV combined with SRS through a prospective trial is urgently needed for patients with BM.…”
supporting
confidence: 51%
“…However, many BM patients are eligible to SRS and it could be assumed that the good safety profile of BEV administration with a large radiation volume may also be expected in the context of its combination with smaller volume as in SRS. This assumption seems confirmed by some recent data of SRS combined with BEV in patients with recurrent malignant gliomas, confirming the feasibility of this approach with a good safety profile (5)(6)(7)(8). Clinical evaluation of BEV combined with SRS through a prospective trial is urgently needed for patients with BM.…”
supporting
confidence: 51%
“…At the time of recurrence, TMZ has been proven to be an effective salvage therapy, with bevacizumab emerging as a potential replacement [3, 9]. MGMT methylation appears to play a role, as prolonged TMZ therapy can substantially deplete MGMT.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of a focal recurrence can lead to prolonged growth control and reduced tumor burden and is favored in younger patients with an initial prolonged disease-free interval in whom recurrence is solid or cystic, circumscribed, and has not infiltrated other vital structures [1, 4, 6, 7]. While previous studies have suggested that surgical resection provides a palliative and local control benefit, prolonged survival has not been observed [8, 9]. Chemotherapy agents have been used with limited success as trials of bevacizumab and irinotecan have demonstrated efficacy in delaying tumor recurrence with minimal long-term benefit, especially after recurrence [6, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Reoperation was performed in 7 cases before they were referred to our clinic; in 6 cases, it was subtotal resection and in 1 case it was gross total resection. SRT was performed in a median of 3 fractions (range 2-5) and the median prescription dose was 20 Gy (range [18][19][20][21][22][23][24][25][26][27][28][29][30], which was biologically equivalent to a dose of 40 Gy (range 28.8-52.8). The SRT parameters were as follows: the median conformity index, the new conformity index, and the homogeneity index were calculated as 1.23 (range 1.08-2.52), 1.29 (range 1.12-7.54), and 1.19 (range 1.09-1.43), respectively.…”
Section: Patient and Treatment Characteristicsmentioning
confidence: 99%
“…in a median of 3 fractions (range 2-5). The median prescription dose was 20 Gy (range [18][19][20][21][22][23][24][25][26][27][28][29][30]. While the median actuarial survival after initial diagnosis for patients treated with salvage SRT was 30 months (range 9-123), it was only 14 months (range 1-111) for patients who could not be treated with salvage SRT (p = 0.001).…”
mentioning
confidence: 99%